PERSEPSI MASYARAKAT TERHADAP KEBERADAAN USAHA PETERNAKAN AYAM RAS PETELUR DI LINGKUNGAN PEMUKIMAN DI NAGARI MUNGKA KECAMATAN MUNGKA KABUPATEN LIMA PULUH KOTA - oktavia, mutiara; Prarikeslan, widya (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
The laying hen farm in Nagari Mungka is close to residential areas which cause unpleasant odors which can pollute the environment which leads to a perception. This research aims to determine the public's perception of the business of egg-laying chicken farming in residential areas in Nagari Mungka, Mungka District, and to find out efforts to overcome the negative impacts caused by egg-laying chicken farming in residential areas in Nagari Mungka. The data analysis used in this research is statistical analysis using a Likers Scale to measure the sub-variables of odor and farm cleanliness. The results of the research show that the public's perception of the existence of egg-laying chicken farming businesses in residential areas in Nagari Mungka, Mungka District is in the moderately disturbed category. Efforts to overcome the negative impacts caused by egg-laying chicken farming by the local community are by taking several measures such as closing the doors and windows of the house when the wind comes, using air freshener, using fans and using fly tape.